THE IMPLEMENTATION OF MULTISTAGE HACKING DEFENSE SYSTEM FOR WIRELESS LANS - Murtadha, Muayad (Iraqi Journal of Science, 2024)
The security of wireless LANs has been a source of concern for businesses and individuals, who are aware of its advantages due to its flexibility, ease of development and reconfiguration. With the increase in the use of wireless LANs for enterprises and homes, where information resources are shared continually, security is of the essence. Wireless security and hacking defense systems becomes an alarming concern as everything being transmitted is available in the air. Encryption and Authentication are seen as major tools in the line of defense of wireless LANs. This paper discusses the various security protocols used in wireless LANs and how effective they are in keeping wireless LANs secure. The risks of using these protocols are outlined, and recommended suggestions for practical multistage hacking defense implementations with modern technologies are detailed. Also, the results of testing experiments for some protocols are presented.